Implementation evaluation of an evidence-based emergency nursing framework (HIRAID): study protocol for a step-wedge randomised control trial. Issue 1 (17th January 2023) - Curtis, Kate; Fry, Margaret; Kourouche, Sarah; Kennedy, Belinda; Considine, Julie; Alkhouri, Hatem; Lam, Mary; McPhail, Steven M; Aggar, Christina; Hughes, James; Murphy, M; Dinh, Michael; et al.
Abstract : Introduction: Poor patient assessment results in undetected clinical deterioration. Yet, there is no standardised assessment framework for >29 000 Australian emergency nurses. To reduce clinical variation and increase safety and quality of initial emergency nursing care, the evidence-based emergency nursing framework HIRAID (History, Identify Red flags, Assessment, Interventions, Diagnostics, communication and reassessment) was developed and piloted. This paper presents the rationale and protocol for a multicentre clinical trial of HIRAID. Methods and analysis: Using an effectiveness-implementation hybrid design, the study incorporates a stepped-wedge cluster randomised controlled trial of HIRAID at 31 emergency departments (EDs) in New South Wales, Victoria and Queensland. The primary outcomes are incidence of inpatient deterioration related to ED care, time to analgesia, patient satisfaction and medical satisfaction with nursing clinical handover (effectiveness). Strategies that optimise HIRAID uptake (implementation) and implementation fidelity will be determined to assess if HIRAID was implemented as intended at all sites. Ethics and dissemination: Ethics has been approved for NSW sites through Greater Western Human Research Ethics Committee (2020/ETH02164), and for Victoria and Queensland sites through Royal Brisbane & Woman's Hospital Human Research Ethics Committee (2021/QRBW/80026). The final phase of the study will integrate the findings in a toolkit for national rollout. A dissemination, communications (variety of platforms) and upscaling strategy will be designed and actioned with the organisations that influence state and national level health policy and emergency nurse education, including the Australian Commission for Quality and Safety in Health Care. Scaling up of findings could be achieved by embedding HIRAID into national transition to nursing programmes, 'business as usual' ED training schedules and university curricula. Trial registration number: ACTRN12621001456842.